2022
DOI: 10.1002/ejhf.2593
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of left atrial changes after optimization of medical therapy in patients with heart failure

Abstract: Limited data exist regarding the prognostic relevance of changes in left atrial (LA) dimensions in patients with heart failure (HF). We assessed changes in LA dimension and their relation with outcomes after optimization of guideline-directed medical therapy (GDMT) in patients with new-onset or worsening HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Up‐titration to higher doses of angiotensin‐converting enzyme inhibitors or angiotensin receptor blockers was independently associated with lower likelihood of LAAR. Furthermore, LAAR was independently associated with an increased risk of the composite of all‐cause mortality or HF hospitalization 18 …”
Section: Atrial Diseasementioning
confidence: 96%
See 1 more Smart Citation
“…Up‐titration to higher doses of angiotensin‐converting enzyme inhibitors or angiotensin receptor blockers was independently associated with lower likelihood of LAAR. Furthermore, LAAR was independently associated with an increased risk of the composite of all‐cause mortality or HF hospitalization 18 …”
Section: Atrial Diseasementioning
confidence: 96%
“…Furthermore, LAAR was independently associated with an increased risk of the composite of all-cause mortality or HF hospitalization. 18 Cardiac amyloidosis may be difficult to diagnose. 19,20 Vergaro et al 21 highlighted the importance of atrial involvement ('atrial amyloidosis'), that might be a consequence of ventricular dysfunction, amyloid infiltration of the atrial wall or cardiotoxic damage following amyloid deposition.…”
Section: Treatmentmentioning
confidence: 99%
“…We thank Yu et al for their comments on our research paper assessing the clinical and prognostic implications of left atrial (LA) structural changes after optimization of medical therapy in patients with heart failure (HF). 1 In the past decades, the concept of LA remodelling has evolved, and the contribution of the left atrium to the pathophysiology of HF has significantly grown. [2][3][4] Indeed, changes in LA structure and function may be either a marker of HF severity and a mechanism actively contributing to the progression of cardiac dysfunction.…”
Section: Reply To the Letter Regarding The Article 'Clinical Implicat...mentioning
confidence: 99%
“…Atrial myopathy underlies a structural and functional derangement associated with an increased risk of the development of atrial fibrillation 8–12 . It has been shown that measures of left atrial sphericity and left atrial volume indexed are independent predictors of atrial fibrillation recurrence after catheter ablation 13 .…”
mentioning
confidence: 99%
“…7 Editorial Atrial myopathy underlies a structural and functional derangement associated with an increased risk of the development of atrial fibrillation. [8][9][10][11][12] It has been shown that measures of left atrial sphericity and left atrial volume indexed are independent predictors of atrial fibrillation recurrence after catheter ablation. 13 Left atrial conduit, instead, depends on noninvasively assessed atrial stiffness and appears to be increased in heart failure patients with the worst survival.…”
mentioning
confidence: 99%